Eksistensi Konsep Nilai â€œLuan dan Tebenâ€ sebagai Pembagian Ruang pada Level Makro Berdasarkan Nilai Tradisional Bali di Wilayah Selatan Kabupaten Badung - Budhiari, Ni Made Dwi Sulistia; Buchori, Imam (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Bali Province has had local wisdom values as conceptual in its territory construction. This conceptual value system is an elaboration applied comprehensively and systematically in every aspect construction. Value concept that animates those elements are inspired by values of culture and translated into a spatial form. Every concept each value has an area that characterize as intermediate (in the middle). This zone system generates region to be designated for certain types of activities, which aim to maintain the balance of macrocosmos and microcosmos. Nowadays, the development that occurred in Badung is under control, due to the existence of Bali as ODTW, resulting in high interest investment, which in turn gives a positive and negative impact. This issue is interesting to be a study, considering the utilization of space in the area of Bali should be attached with the concept of macro space division implied in the positive rule. Based on the analysis by making a comparison between the map overlay spatial through the value concept